Neuroendoscopic surgery versus external ventricular drainage alone or with intraventricular fibrinolysis for intraventricular hemorrhage secondary to spontaneous supratentorial hemorrhage: a systematic review and meta-analysis. - Yuping Li; Hengzhu Zhang; Xiaodong Wang; Lei She; Zhengcun Yan; Nan Zhang; Renfei Du; Kaixuan Yan; Enxi Xu; Lujun Pang (PLoS ONE)
Background and purpose Although neuroendoscopy (NE) has been applied to many cerebral diseases, the effect of NE for intraventricular hemorrhage (IVH) secondary to spontaneous supratentorial hemorrhage remains controversial. The purpose of this study was to analyze the effect of NE compared with external ventricular drainage (EVD) alone or with intraventricular fibrinolysis (IVF) on the management of IVH secondary to spontaneous supratentorial hemorrhage. Methodology/ principal findings A systematic search of electronic databases (PubMed, EMBASE, OVID, Web of Science, The Cochrane Library, CBM, VIP, CNKI, and Wan Fang database) was performed to identify related studies published from 1970 to 2013. Randomized controlled trials (RCTs) or observational studies (OS) comparing NE with EVD alone or with IVF for the treatment of IVH were included. The quality of the included trials was assessed by Jaded scale and the Newcastle-Ottawa Scale (NOS). RevMan 5.1 software was used to conduct the meta-analysis. Results Eleven trials (5 RCTs and 6 ORs) involving 680 patients were included. The odds ratio (OR) showed a statistically significant difference between the NE + EVD and EVD + IVF groups in terms of mortality (OR, 0.31; 95% CI, 0.16-0.59; P=0.0004), effective hematoma evacuation rate (OR, 25.50, 95%CI; 14.30, 45.45; P<0.00001), good functional outcome (GFO) (OR, 4.51; (95%CI, 2.81-7.72; P<0.00001), and the ventriculo-peritoneal (VP) shunt dependence rate (OR, 0.16; 95%CI; 0.06, 0.40; P<0.0001). Conclusion Applying neuroendoscopic approach with EVD may be a better management for IVH secondary to spontaneous supratentorial hemorrhage than NE + IVF. However, there is still no conclusive evidence regarding the preference of NE vs. EVD alone in the case of IVH, because insufficient data has been published thus far. This study suggests that the NE approach with EVD could become an alternative to EVD + IVF for IVH in the future.